Nest site selection of cavity-nesting birds at Jahangirnagar University campus, Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2024)
Understanding nest site selection by cavity-nesting birds is important for their conservation implications. We examined the preferences and characteristics of nesting trees and cavities used by cavity-nesting birds at Jahangirnagar University (JU) campus from January 2020 to October 2021. A total of 30 tree- cavity nests of 11 species of birds belonging to 4 orders and 7 families were recorded where 36% were primary excavators and 64% were secondary cavity-nesters. Out of 14 species of trees used in cavity-nesting, the most of the nests were built in Mahogany Swietenia mahagoni (n=8) followed by White siris Albizia procera (n=6) and Rain tree Samania saman (n=3). Diameter at breast height (DBH) of the nesting trees varied from 27 cm to 112 cm (52±23.2 cm). The highest mean DBH was recorded in Samania saman (85 cm) followed by Swietenia mahagoni (67 cm). Common Myna showed the widest selection of nesting tree species (n=9) followed by Black-rumped Flameback (n=4) and Lineated Barbet (n=4). Majority of the nesting trees (87%) were found in roadside (within 1-5 m) vegetation while 60% nesting trees located within 30 m from the nearby water bodies. The cavity-nesting species preferred to nest between 2 m to 12 m (5.2±2.6 m) height from the ground level. The entrance width and the depth of tree holes (n=30) used by cavity-nesters varied from 5 cm to 22 cm (7.5±3.5 cm) and 13 cm to 45 cm (23.2±6.5 cm), respectively. Suitable cavities are critical for reproductive success of cavity-nesting birds and our results highlight the conservation value of cavity-bearing large trees to maintain a healthy population of cavity-nesting birds at JU campus.Jahangirnagar University J. Biol. Sci. 12(1 & 2): 1-10, 2023 (June & December)